2015
DOI: 10.1094/pdis-09-13-0936-re
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Using Rootstocks with Resistance to Ralstonia solanacearum Against Meloidogyne incognita in Tomato Production

Abstract: Root-knot nematodes (RKNs; Meloidogyne spp.) and Ralstonia solanacearum, the causal agent of bacterial wilt, are major soilborne pathogens in U.S. tomato production. Methyl bromide has been used for decades to effectively manage RKN but its phase-out and the high cost of other effective fumigants such as 1,3-dichloropropene has resulted in a need to develop sustainable alternatives. Many of the commercially popular varieties used by the tomato industry do not have resistance to RKNs and R. solanacearum. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
5
24
1
1
Order By: Relevance
“…Leonardi & Giuffrida (2006) grafted tomato hybrid Rita F1 on three commercial rootstocks and showed that one of the rootstocks excelled in yield compared with the others, which is consistent with our study. Also, Kunwar et al (2014), evaluating the technique of grafting in tomato, noted that the yield of ungrafted treatments considerably outweighed treatments with grafting, regardless of the method, which does not agree with the data obtained in this study, in which rootstock IAC391 showed no significant differences when compared with the ungrafted control. Likewise, Bernal et al (2016), who studied grafted string beans to improve performance in production, noted that one treatment obtained the best results for variable total yield per plant compared with other treatments, both grafted and ungrafted.…”
Section: Total Productioncontrasting
confidence: 96%
“…Leonardi & Giuffrida (2006) grafted tomato hybrid Rita F1 on three commercial rootstocks and showed that one of the rootstocks excelled in yield compared with the others, which is consistent with our study. Also, Kunwar et al (2014), evaluating the technique of grafting in tomato, noted that the yield of ungrafted treatments considerably outweighed treatments with grafting, regardless of the method, which does not agree with the data obtained in this study, in which rootstock IAC391 showed no significant differences when compared with the ungrafted control. Likewise, Bernal et al (2016), who studied grafted string beans to improve performance in production, noted that one treatment obtained the best results for variable total yield per plant compared with other treatments, both grafted and ungrafted.…”
Section: Total Productioncontrasting
confidence: 96%
“…McAvoy et al (2012) found that plants grafted to 'RST-04-106-T' did have a lower disease incidence and higher yields in fields naturally infested with Ralstonia solanacearum when compared with nongrafted and self-grafted controls, but this trend was found in only 1 of the 2 years examined. Kunwar et al (2015) found that the use of 'RST-04-106-T' reduced the incidence of root gall in conditions where root-knot nematodes (Meloidogyne incognita) were present, but this did not significantly increase yield over nongrafted controls. These two studies point out that, even in the presence of soil-borne disease, 'RST-04-106-T' may not be the best choice.…”
Section: Discussionmentioning
confidence: 97%
“…Research examining the rootstock 'RST-04-106-T' has been somewhat limited, and has largely focused on performance in conditions where disease is present (Kunwar et al, 2015;McAvoy et al, 2012). McAvoy et al (2012) found that plants grafted to 'RST-04-106-T' did have a lower disease incidence and higher yields in fields naturally infested with Ralstonia solanacearum when compared with nongrafted and self-grafted controls, but this trend was found in only 1 of the 2 years examined.…”
Section: Discussionmentioning
confidence: 99%
“…Tomato production in the tropics and subtropics, however, is severely affected by bacterial wilt disease, caused by Ralstonia solanacearum species complex ( RSSC ; Safni et al, ). The RSSC are soil‐borne bacteria which can attack >450 plant species in 50 families, including pepper, potato, tobacco, eggplant, ginger, banana and several other economically important crops (Hayward, ; Janse et al, ; Kunwar, Iriarte, et al, ; Kunwar, Paret, et al, ; Kunwar et al, ; Poussier et al, ). The pathogen exhibits wide phenotypic and genotypic variation and can survive for extended periods in irrigation water, soil and rhizosphere (Van Elsas et al, ; Van Elsas, Kastelein, Bries, & Overbeek, ).…”
Section: Introductionmentioning
confidence: 99%